Spectrophotometric Study of the Interaction of Platinum(IV) with New Derivatives of Azolidones - Tymoshuk, Oleksandr; Oleksiv, Lesia; Rydchuk, Petro; Chaban, Taras; Tymoshuk, Svitlana; Matiychuk, Vasyl (Видавництво Львівської політехніки, 2020)
Спектрофотометричним методом досліджено взаємодію йонів Pt(IV) з новими похідними азолідонів. Розроблено методику спектрофотометричного визначення платини(IV) за допомогою 5-гідроксиіміно-4-іміно-1,3-тіазолідин-2-ону за рН 5,0 у середовищі ацетатного буферу. Запропонований метод було апробовано під час визначення Pt(IV) у модельних розчинах та металічному сплаві.

The interaction of Pt(IV) ions with the new derivatives of azolidones by spectrophotometric method was investigated. The spectrophotometric method for the determination of Pt(IV) using 5-hydroxyimino-4-imino-1,3- thiazolidine-2-one at pH 5.0 in acetate buffer medium was elaborated. The proposed method was tested by determination of Pt(IV) in model solutions and metallic alloy.
Спектрофотометричне дослідження взаємодії платини(IV) з новими похідними азолідонів
Keywords: спектрофотометрія; платина(IV); азолідони; комплекс; spectrophotometry; platinum(IV); azolidones; complex